The Effect of Chronic Energy Deficiency, Anemia, and Compliance with Iron Supplement Consumption in Pregnant Women on Low Birth Weight - Yanti, Fitria Dwi; Ginting, Riska Mayang Saputri; Susanti, Elvi (Media Publikasi Cendekia Indonesia, 2024)
This study aims to determine the effect of chronic energy deficiency, anemia, and compliance with the consumption of iron supplement tablets by pregnant women with low birth weight. This research design was a case-control retrospective approach with a sample size of 33 people. The independent variables in this study were chronic energy deficiency, anemia, and compliance with iron supplement consumption during pregnancy; the dependent variable was Low Birth Weight (LBW). Data collection using observation and interviews, statistical tests using the chi-square test. The results of the research were that there was an effect of Chronic Energy Deficiency (CED) (p=0.000) OR=94.5, anemia (p=0.019) OR=9.64, compliance with iron supplement consumption on LBW (p=0.009) OR=12.00. An OR value > 1 proves that pregnant women with CED anemia and compliance with iron supplement consumption have a greater risk of giving birth to LBW children than mothers without CED are anemic and adhere to iron supplement consumption. The incidence of CED, anemia, and compliance with iron supplement consumption in pregnant women influence LBW. Prevention efforts need to be carried out through education and assistance from families in meeting the nutritional needs of pregnant women, as well as compliance in consuming iron supplements as recommended